High- or moderate-intensity training promotes change in cardiorespiratory fitness, but not visceral fat, in obese men: A randomised trial of equal energy expenditure exercise - Gerosa-Neto, José [UNESP]; Panissa, Valéria Leme Gonçalves; Monteiro, Paula Alves [UNESP]; Inoue, Daniela Sayuri [UNESP]; Ribeiro, José Procópio Jabur; Figueiredo, Caique [UNESP]; Zagatto, Alessandro Moura [UNESP]; Little, Jonathan Peter; Lira, Fabio Santos [UNESP] (Elsevier, 2019)
This study compared the effects of two exercise programs performed in different intensities, but equal overall energy expenditure (EE). Adult men with obesity (29.6 ± 4.9 years; BMI = 35.1 ± 3.3 kg/m2)were randomised to one of three groups: High-intensity interval training (HIIT- 10 × 1:1 min 100% VO2max; n = 13); Moderate-intensity continuous training (MICT - ˜35 min 65% VO2max; n = 13)or Control (no training; n = 6). The session EE (HIIT = 278.0 ± 37.1; MICT = 299.4 ± 17.8 kcal)was calculated by adding the aerobic contribution (VO2 of the session minus VO2 at rest)and anaerobic (difference between the VO2 estimated and VO2 measured in session). The anaerobic contribution in HIIT was 30%, showing that a substantial portion of the energy for 10 x 1 min HIIT comes from non-oxidative metabolism. VO2max improved in both trained groups (p = 0.006), while systolic blood pressure decreased (p < 0.001)and diastolic blood pressure was not altered. Visceral and subcutaneous fat stores did not change after the intervention, indicating a longer intervention may be necessary for changes in adiposity. Six weeks of HIIT or MICT were effective in improving cardiorespiratory fitness and blood pressure in previously inactive obese men.
Keywords: Blood pressure; Fat mass; Isocaloric training; Leptin; Obesity; Time-efficiency